Maybe It’s Time to change the Order of the Seimas Elections? - Tučas, Rolandas; Kanapka, Giedrius (Politologija, 2022)
This article discusses the problems of the mixed parallel voting electoral system applied in the Seimas elections, paying more attention to its geographical aspect – the problems caused by the frequent redrawing of single-member constituencies due to demographic processes. The article presents the principles and methods of electoral constituency delimitation in other countries, the experience gained during the redrawing of the boundaries of single-member constituencies for the 2016 and 2020 Seimas elections, and highlights the problems encountered. The problems of the Lithuanian electoral system discussed in the article are recommended to be solved in the future by using only proportional representation for the election of the Seimas, dividing the state into 6 multi-member constituencies (the 7th constituency is for citizens of our country living abroad), which would be formed on the basis of counties, merging smaller counties together. A similar procedure for the election of the Seimas in Lithuania was applied in the third decade of the 20th century, therefore, this reform should be called the restitution of the interwar parliamentary elections.
Keywords: Seimas elections of the Republic of Lithuania; electoral systems; single-member constituencies (electoral disctricts); multi-member constituencies (electoral disctricts); electoral wards